Pendampingan Penyusunan Anggaran untuk Keberlanjutan Bisnis UMKM Desa Cigugur Girang Kabupaten Bandung Barat - Hastuti; Noer Ridha, Noorsyah Adi; Mauluddi, Hasbi Assidiki; Gunawan, Arwan; Ruhana, Nafisah; Nurmalina, Rina (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (PKM) entitled “Budget Planning Assistance for Business Sustainability of MSMEs in Cigugur Girang Village” aims to improve financial literacy and budgeting skills among MSME actors. This program was implemented using a Service Learning approach, integrating training on financial planning, the use of budgeting worksheets, and assistance in preparing operational, cash, and sales budgets. Evaluation results showed a significant improvement in participants’ ability to manage finances, control cash flow, and make more strategic business decisions. Although challenges remain, such as limited digital literacy and resource constraints, the program proved effective in strengthening MSME capacity. This program initiative contributes to empowering MSMEs to achieve business sustainability and competitiveness, while also having a positive impact on the local economy.